News programs: Designing MSNBC.com's online interfaces. (January 2015) - Braun, Joshua A
In this essay, I use Law's framework of heterogeneous engineering in tandem with insights from other sociologists of systems and scholarship on organizations, as a springboard to examine a number of digital artifacts assembled by the MSNBC Digital Network over the period 2007 through 2010 and to explore the manner in which a wide variety of values, interests, and concerns became 'invested and contested' in their design. Specifically, this article, the result of 5 weeks of interviewing and field observation at MSNBC.com, MSNBC TV, and National Broadcasting Corporation (NBC) News' various online offices, explores the backstories of two seemingly mundane interfaces used by NBC News' Web properties during that period, both of which are revealed to be particularly dynamic, heterogeneous, contingent, and consequential.